THE EFFECT OF LEARNING ACTIVITIES ON ACCOUNTING LEARNING RESULTS FOR CLASS XII IPS STUDENTS UPT SMA NEGERI 11 LUWU UTARA - Edhy, Ikram; Azis, Fajriani; Hasyim, Sitti Hajerah; Tikollah, M. Ridwan; Idris, Hariany (Universitas Labuhanbatu, 2023)
This study aims to analyze the effect of learning activities on the results of studying accounting in class XII IPS UPT SMA Negeri 11 Luwu Utara. The variables of this study are learning activities as the independent variable (X) and learning outcomes as the dependent variable (Y). The population of this study were all students of class XII IPS UPT SMA Negeri 11 North Luwu, totaling 64 students, while the sample used a saturated sampling technique with a total sample of 64 students. Data collection techniques used are questionnaires, observation, and documentation. The data analysis technique used is descriptive statistical analysis, instrument testing and hypothetical testing using SPSS 25 for windows. The results of this study indicate that: Based on the results of simple linear regression analysis, the equation model Y = 48.671 + 0.469 X is obtained, which means that for each addition of one learning activity value, the value of accounting learning outcomes for class XII IPS students increases by 0.469 units. From the results of the t-test analysis, the significance is 0.000 <0.05, which means that the learning activity variable has a positive and significant effect on the accounting learning outcomes of class XII IPS UPT SMA Negeri 11 Luwu Utara, thus the hypothesis is